Wideband Acoustic Immittance in Children - Shahnaz, Navid; Aithal, Sreedevi; Bargen, Gabriel A. (Seminars in Hearing, 2023)
As wideband absorbance (WBA) gains popularity, it is essential to understand the impact of different middle ear pathologies on the absorbance patterns as a function of frequency in children with various middle ear pathologies. More recently, the use of wideband tympanometry has enabled clinicians to conduct WBA at ambient pressure (WBAamb) as well as the pressurized mode (WBATPP). This article reviews evidence for the ability of WBA measurements to accurately characterize the normal middle ear function across a wide range of frequencies and to aid in differential diagnosis of common middle ear disorders in children. Absorbance results in cases of otitis media with effusion, negative middle ear pressure, Eustachian tube malfunction, middle ear tumors, and pressure equalization tubes will be compared to age-appropriate normative data. Where applicable, WBAamb as well as WBATPP will be reviewed in these conditions. The main objectives of this article are to identify, assess, and interpret WBAamb and WBATPP outcomes from various middle ear conditions in children between the ages of 3 and 12 years.
Keywords: wideband acoustic immittance; wideband absorbance tympanometry; middle ear dysfunction; children; pediatric